Civil service reform in Kazakhstan: trajectory to the 30 most developed countries?. (September 2019) - Janenova, Saltanat; Knox, Colin
Kazakhstan has ambitious plans to become one of the top 30 developed countries in the world by 2050. Its most recent route map to achieve this is the Plan for the Nation : 100 Concrete Steps, announced by the president in May 2015. A key pillar in this reform agenda is the development of a professional civil service. This article considers whether civil service reforms to date and those envisaged under the new plan offer a trajectory to the 2050 stated goal. It finds that despite significant political endorsement at the highest level, reforms have focused on institutional, structural and legal changes without the necessary attention to how these will impact on the quality of public services provision. The article highlights the interdependence between civil service reforms and an outcomes-based approach and adapts the Organisation for Economic Co-operation and Development's Better Life framework for Kazakhstan as a way of making this connection. Points for practitioners: Moving to an outcomes-based approach in a developing country challenges practitioners to focus on the impact of their work and to be judicious and context-specific in the selection of results indicators.